Adsorption and Photocatalytic Activity of Bentonite–Titanium Dioxide on The Degradation of Methylene Blue Dyes - Muhammad Said; Niko Erlangga; Daniel Alfarado; Suheryanto Suheryanto; Elisa Nurnawati (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
The aim of this research is to determine the effect of bentonite-Titanium dioxide (Benonite-TiO2) composite on the degradation process of methylene blue. It was carried out by synthesizing the composite through the impregnation of Titanium dioxide (TiO2) on bentonite and then characterizing the obtained compound using XRD and SEM-EDX. The results of the XRD characterization showed that there was a shift in the diffraction angle (2θ), which indicated the success of the impregnation procedure. The morphology of the composite showed that the bentonite surface had been filled with TiO2, as evidenced by the results of the EDX analysis, which showed a 7.03% increase in Titanium. Furthermore, the degradation process was carried out using various variables, including contact time, the ratio of composite weight to dye, and by irradiation with a UV lamp at a wavelength of 352 nm UV. It was discovered that the best degradation in the concentration of methylene blue occurred at a maximum contact time of 90 minutes and at a maximum weight of 10 mg of benonite-TiO2, with an effectiveness of 99.91% after irradiation and 92.26% without irradiation.